Analysis of Workload and Physical Work Environment on Job Satisfaction in Honorary Teachers at SDN 059 Cirangrang, Bandung City - Andara Rossa Kusuma; Khaerul Rizal Abdurahman (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Education is one of the important factors in creating quality human resources. In the world of education, teachers have a crucial role in supporting the success of the teaching and learning process, so teacher job saticfaction needs to be considered in order to improve the quality of learning. From the result of interviews and observations obtained several problems related to the job satisfaction of honorary teachers, which are reflected in the innappropriate workload and suboptimal physical work environment conditions such as the lack of natural lighting (sunlight). This study aims to analyze the workload and physical work environment on job satisfaction of honorary teachers at SDN 059 Cirangrang, Bandung City. The method used in this study is a qualitative method with data collection techniques through interviews, observation and documentation. Data validity testing was carried out using data triangulation, in this study the number of informants was five honorary teachers and one key informant. This study shows the results that the workload of honorary teachers at SDN 059 Cirangrang is in the high category, but can still be adjusted to the abilities and competencies og teachers. Furthermore, the physical work environment at SDN 059 Cirangrang is still considered inadequate due to limited facilities and uncomfortable working conditions. Consequently, both workload and the physical work environment impact to job saticfaction. It can be concluded that a workload that aligns with competencies and abilities, supported by comportable physical work environment, will increase job satisfaction among honorary teachers.